2021
DOI: 10.1089/cell.2020.0078
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Cytoplast Arrest and Morula Aggregation Enhance Development, Cryoresilience, andIn VivoSurvival of Cloned Sheep Embryos

Abstract: Zona-free somatic cell transfer (SCT) and embryo aggregation increase throughput and efficiency of cloned embryo and offspring production, respectively, but both approaches have not been widely adopted. Cloning efficiency is further improved by cell cycle coordination between the interphase donor cell and metaphasearrested recipient cytoplast. This commonly involves inclusion of caffeine and omission of calcium to maintain high mitotic cyclin-dependent kinase activity and low calcium levels, respectively, in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…Among these documents, 10 had no record of citations. The most recent document was by McLean et al [42] who studied the effect of embryo aggregation during the vitrification process of cloned sheep embryos. They observed that the aggregated embryos had an in vivo survival rate similar to that of the group that was not vitrified.…”
Section: Most Cited Documentsmentioning
confidence: 99%
“…Among these documents, 10 had no record of citations. The most recent document was by McLean et al [42] who studied the effect of embryo aggregation during the vitrification process of cloned sheep embryos. They observed that the aggregated embryos had an in vivo survival rate similar to that of the group that was not vitrified.…”
Section: Most Cited Documentsmentioning
confidence: 99%
“…Among these articles, 10 articles had no record of citations. The most recent article was by McLean et al [42] who studied the effect of embryo aggregation during the vitrification process of cloned sheep embryos. They observed that the aggregated embryos had an in vivo survival rate similar to that of the group that was not vitrified.…”
Section: Most Cited Articlesmentioning
confidence: 99%
“…For one, the principled approach of the infer package has made it an especially good fit for teaching introductory statistics and data science (Baumer et al, 2020;Çetinkaya-Rundel & Ellison, 2021;Ismay & Kim, 2019) and research in data pedagogy (Fergusson & Pfannkuch, 2021;Loy, 2021). Further, the package has already seen usage in a number of published scientific applications (Ask et al, 2021;Fallon & Hinds, 2021;McLean et al, 2021). Finally, the package integrates with the greater tidymodels collection of packages, a burgeoning software ecosystem for tidyverse-aligned predictive modeling used across many modern research and industrial applications (Kuhn & Wickham, 2020).…”
Section: Statement Of Needmentioning
confidence: 99%